Forced Displacement and the Labor Market in the Main Cities of Colombia - Valencia Agudelo, Germán Darío; Montoya Polanco, Juan David; Loaiza Mejía, Davidson (Sociedad y Economía, 2019)
The internal armed conflict in Colombia has caused the forced displacement of millions of victims to the maincities of the country, affecting the dynamics of labor markets. From the study of the dynamics of forced migration in the country, measured through means difference tests, pressure and intensity indicators, and a literary review of forced and economic migration, the work analyzes the integration of the displaced in the labor markets in the 23 main cities of the country and describes its possible labor effects. It shows that displaced people fail in their economic integration as a result of the additional obstacles they face to work. In addition, the estimation of the effects of this integration is still ambiguous due to methodological problems.